Theory as time travel: Patomäki, World Statehood and possible futures. - Morgan, Jamie (Journal of Critical Realism, 2024)
In this review essay, I set explore Heikki Patomäki's seventh sole-authored book in English, World Statehood. I set out the thematic structure and chapter order and then address whether the concept of 'self-transformative capacity of contexts' implies a central conflation and what is assumed if one argues that there is a tendential form of civilizational progress. I conclude with discussion of a causal process theory of time.